2022
DOI: 10.3390/biom12091220
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Compounds Inhibit Osteoclast Differentiation While Reducing Autophagy through Limiting ROS and the Mitochondrial Membrane Potential

Abstract: Polyphenolic compounds are a diverse group of natural compounds that interact with various cellular proteins responsible for cell survival, differentiation, and apoptosis. However, it is yet to be established how these compounds interact in myeloid cells during their differentiation and the molecular and intracellular mechanisms involved. Osteoclasts are multinucleated cells that originate from myeloid cells. They resorb cartilage and bone, maintain bone homeostasis, and can cause pathogenesis. Autophagy is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…As described previously ( 13 , 15 ), ECSIT deleted macrophages had lower Δψm when compared to control cells. RANKL is known to increase Δψm by stimulating OXPHOS ( 18 , 19 ). Accordingly, RANKL increased Δψm in control cells while this response was abrogated in cells lacking ECSIT ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…As described previously ( 13 , 15 ), ECSIT deleted macrophages had lower Δψm when compared to control cells. RANKL is known to increase Δψm by stimulating OXPHOS ( 18 , 19 ). Accordingly, RANKL increased Δψm in control cells while this response was abrogated in cells lacking ECSIT ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that TRIM45 regulated NLRP3 in an Atg5-dependent manner. Considering the correlation between autophagy, ROS and mitochondrial membrane potential [ 54 , 55 ], we also examined the changes in these indices in the different groups. The results showed that knocking down TRIM45 could improve mitochondrial membrane potential and reduce ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial membrane potentials (MMP) were determined by JC-1 staining as described previously [ 29 , 30 ] ; experiments were set as described above. The DPSC ℗ -treated cells and untreated cells were incubated in 5 μM of JC-1 dye for 15 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%